Classification of software project risk managers: Established on roles and responsibilities - Janjua, U.I. (Institute of Electrical and Electronics Engineers Inc., 2014)
Generally, people have used the term 'risk manager' in different fields of science to represent a person who is responsible for handling risk management activities. However, in the field of software engineering, the term 'risk manager' is not well defined and there is ambiguity over the term's meaning. The main objective of the paper is to review the literature thematically in order to make the terms understandable and to find the role of a risk manager for effective software project risk management. Additionally, in the end of the paper different title of software project risk managers has been classified on the base of their roles and responsibilities. Â© 2014 IEEE.